T TANTANGAN, PELUANG, DAN STRATEGI PENDIDIKAN KRISTEN PADA ERA DISRUPSI - Purwisasi Yuli; Sannur Tambunan; Titus Karbui; Roy Damanik; Yulianus Bani (CARAKA: Jurnal Teologi Biblika dan Praktika, 2022)
Research on Christian education strategies in the era of disruption really needs to be done as the church's readiness to face the challenges of this era. The church needs to base its teaching on the teachings and actions of the Lord Jesus through His words in the Bible. Christian education today faces many challenges, with the ease of accessing any information, everyone tends to have an interest in being alone, because they are too preoccupied with online media that they access and have quite a negative influence. This study aims to find the challenges of Christian education in the era of disruption, opportunities and strategies for Christian education in the era of disruption. The research method used in this study is a qualitative approach with a descriptive method. Through research, it was found that the rapid development of technology has become a challenge for Christian education during the period of disruption. In addition, by utilizing existing technology, it is an opportunity for Christian education to be more easily conveyed to the wider community without limits. The strategy that can be done is that Christian education must be delivered with technology that is currently being developed and used by the wider community.